The Distribution of Calcium Buffering Proteins in the Turtle Cochlea - Hackney, Carole M. (J Neurosci, 2003)
Hair cells of the inner ear contain high concentrations of calcium-binding proteins that limit calcium signals and prevent cross talk between different signaling pathways during auditory transduction. Using light microscope immunofluorescence and post-embedding immunogold labeling in the electron microscope, we characterized the distribution of three calcium-buffering proteins in the turtle cochlea. Both calbindin-D28k and parvalbumin-β were confined to hair cells in which they showed a similar distribution, whereas calretinin was present mainly in hair-cell nuclei but also occurred in supporting cells and nerve fibers. The hair-cell concentration of calbindin-D28k but not of parvalbumin-β increased from the low- to high-frequency end of the cochlea. Calibration against standards containing known amounts of calcium-buffering protein processed in the same fluid drop as the cochlear sections gave cytoplasmic concentrations of calbindin-D28k as 0.13–0.63 mm and parvalbumin-β as ∼0.25 mm, but calretinin was an order of magnitude less. Total amount of Ca (2+)-binding sites on the proteins is at least 1.0 mm in low-frequency hair cells and 3.0 mm in high-frequency cells. Reverse transcription-PCR showed that mRNA for all three proteins was expressed in turtle hair cells. We suggest that calbindin-D28k and parvalbumin-β may serve as endogenous mobile calcium buffers, but the predominantly nuclear location of calretinin argues for another role in calcium signaling. The results support conclusions from electrophysiological measurements that millimolar concentrations of endogenous calcium buffers are present in turtle hair cells. Parvalbumin-β was also found in both inner and outer hair cells of the guinea pig cochlea.